2020
DOI: 10.1177/1526602820934762
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Iliac Branch Devices and Their Midterm Performance in Maintaining Blood Flow to the Internal Iliac Artery

Abstract: Purpose: To compare and contrast the midterm outcomes of the E-liac and Zenith (ZBIS) iliac branch devices (IBDs) for the preservation of the internal iliac artery (IIA) in aneurysms involving the iliac bifurcation. Materials and Methods: Between January 2014 and December 2018, 84 consecutive patients (median age 74 years; 76 men) were electively treated with the E-liac (n=44) or ZBIS (n=40) IBDs and were retrospectively analyzed to evaluate the technical success, patency, need for reintervention, and mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
6
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
3
6
1
Order By: Relevance
“…Haulon et al and Karthikesalingam et al both reported similar, slightly elevated occlusion rates of 11.3–12.2% [ 4 , 19 ]. However, our iliac patency rate was lower than what was mostly found in other similar studies, where the internal iliac branch patency was between 89.7% and 100% [ 12 , 20 ].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Haulon et al and Karthikesalingam et al both reported similar, slightly elevated occlusion rates of 11.3–12.2% [ 4 , 19 ]. However, our iliac patency rate was lower than what was mostly found in other similar studies, where the internal iliac branch patency was between 89.7% and 100% [ 12 , 20 ].…”
Section: Discussioncontrasting
confidence: 86%
“…Haulon et al achieved a technical success rate of 94% [ 4 ]. Mylonas et al demonstrated an outstanding technical success rate of 100%, although they reported their results in accordance with more permissive criteria [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 One of the most common causes of failure is kinking secondary to the increasing diameter and length of the growing aortoiliac aneurysm, which can occur in almost any of the joints involving the iliac branch, the bridging stent, or the iliac limb extension. 4 Most kinking-related occlusions occur within the first month, as Mylonas and colleagues 4 also noticed. Balloon-expandable or selfexpanding bridging stents can be used.…”
mentioning
confidence: 88%
“…Another challenge is the risk of external iliac graft limb kinking in the first segment of the EIA. In the study by Mylonas et al, 4 4 patients suffered from EIA thrombosis during the first month and needed a reintervention. Takeoff artery angle may be increased after deployment in some cases, especially in the presence of severe calcification.…”
mentioning
confidence: 97%
See 1 more Smart Citation